Design and Development of Leaf Splitting Unit for Aloe Vera Gel Expulsion Machine. Issue 4 (19th May 2014) - Chandegara, V.K.; Varshney, A.K.
Abstract In this investigation, leaf‐splitting unit was designed and fabricated for Aloe vera gel expulsion machine. The splitting unit consisted of grip roller, reciprocating blade, rotary disc and eccentric drive. The rotary motion was converted into the reciprocating drive with slanted rotary disc mounted on shaft. The grip roller was covered with spongy material to hold the A. vera leaf without breaking rind. The design parameters included were grip roller dimensions and speed, stroke of reciprocating blade and size of rotary disc. The leaf was inserted between two grip rollers and splitting into two halves carried out by reciprocating knife. The splitting unit was tested for different speed of grip expulsion roller and leaf thickness. It was concluded that for getting maximum gel recovery, minimum residual gel percentage, highest expulsion efficiency and output capacity, the leaves should be split in splitting unit and the A. vera gel expulsion should be carried out at 75 rpm roller speed for 25–30‐mm thickness of A. vera leaves. Practical Applications Gel extraction from A. vera leaves is important process as it is used as preservative coating, food drinks and cosmetics. Squeezing of A. vera leaves leads mixing of compounds from leaf skin and deteriorates the quality of gel. The leaf‐splitting process is necessary to reduce the contamination of inner A. vera gel during gel expulsion by preventing ingress of chemical ingredients from leaf skin and maintain its cosmetic and nutritional values. The developed leaf‐splitting unit would reduce manual contact and minimize the processing time to get good quality gel from A. vera leaves without contamination.